Protocol for a clinical trial of text messaging in addition to standard care versus standard care alone in prevention of type 2 diabetes through lifestyle modification in India and the UK - Thomson,HH; Srivanichakorn,W; Oliver,N; Godsland,I; Darzi,A; Majeed,A; Johnston,D (BMC Endocrine Disorders, 2018)
BackgroundType 2 diabetes is a serious clinical problem in both India and the UK. Adoption of a healthy lifestyle through dietary and physical activity modification can help prevent type 2 diabetes. However, implementing lifestyle modification programmes to high risk groups is expensive and alternative cheaper methods are needed. We are using a short messaging service (SMS) programme in our study as a tool to provide healthy lifestyle advice and an aid to motivation. The aim of the study is to assess the efficacy and user acceptability of text messaging employed in this way for people with pre-diabetes (HbA1c 6.0% to ≤6.4%; 42–47 mmol/mol) in the UK and India.Methods/designThis is a randomised, controlled trial with participants followed up for 2 years. After being screened and receiving a structured education programme for prediabetes, participants are randomised to a control or intervention group. In the intervention group, text messages are delivered 2–3 times weekly and contain educational, motivational and supportive content on diet, physical activity, lifestyle and smoking. The control group undergoes monitoring only. In India, the trial involves 5 visits after screening (0, 6, 12, 18 and 24 months). In the UK there are 4 visits after screening (0, 6, 12 and 24 months). Questionnaires (EQ-5D, RPAQ, Transtheoretical Model of Behavioural Change, and food frequency (UK)/24 h dietary recall (India)) and physical activity monitors (Actigraph GT3X+ accelerometers) are assessed at baseline and all follow-up visits. The SMS acceptability questionnaires are evaluated in all follow-up visits. The primary outcome is progression to type 2 diabetes as defined by an HbA1c of 6.5% or over(India) and by any WHO criterion(UK). Secondary outcomes are the changes in body weight, body mass index, waist circumference, blood pressure, fasting plasma glucose; lipids; proportion of participants achieving HbA1c ≤6.0%; HOMA-IR; HOMA-β; acceptability of SMS; dieta